2021
DOI: 10.3389/fphar.2021.669269
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Qinghao Biejia Decoction in the Treatment of Systemic Lupus Erythematosus: A Systematic Review and Meta-Analysis

Abstract: Objective: This meta-analysis aimed to systematically assess the therapeutic efficacy and safety of Qinghao Biejia decoction combined with conventional chemical medicine in patients with systemic lupus erythematosus (SLE), and to provide reference for clinical medication.Methods: Multiple databases were retrieved by computer for randomized controlled trials (RCTs) of treating SLE with Qinghao Biejia decoction combining chemical medicine, from the establishment of the database to January 2021. Study screening, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…[21] QH and BJ are both sovereign herbs in QH-BJ decoction which is taken as a predominant prescription for SLE patients with Yin deficiency syndrome. [8] Studies have shown that the decoction can alleviate the progression of SLE by suppressing the production of Th17 cells and IL-17 in MRL/lpr mice. [22,23]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[21] QH and BJ are both sovereign herbs in QH-BJ decoction which is taken as a predominant prescription for SLE patients with Yin deficiency syndrome. [8] Studies have shown that the decoction can alleviate the progression of SLE by suppressing the production of Th17 cells and IL-17 in MRL/lpr mice. [22,23]…”
Section: Discussionmentioning
confidence: 99%
“…[7] TCM has been proven to be safe and effective in the treatment of SLE, especially in improving patients' symptoms and quality of life. [8] When combined with GCs, TCM shows a good synergistic effect by not only improving the treatment effect, but also reducing the dose of GCs and further promoting their withdrawal. Besides, it can prevent adverse reactions caused by GCs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditional Chinese medicine (TCM) has rich experience in treating SLE with a wide variety of therapies. TCM not only improves the symptoms and the quality of survival of SLE patients but also reduces the side effects of glucocorticoid drugs and is cost-effective, thus it is a common treatment for SLE in Chinese clinics [ 8 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was one of the main prescriptions used in ancient China. In a modern pharmacological study, 1 QBD was shown to exert antipyretic, antipathogenic, and anti‐inflammatory effects and to improve immunity and sedation. It can be used in the clinical treatment of cancer fever, various inflammatory conditions, recurrent fever from multi‐drug resistant bacterial infections, rheumatic immune disease, and climacteric syndrome 2…”
Section: Introductionmentioning
confidence: 99%